Effects of bamboo shoots (Bambusa balcooa) on thyroid hormone synthesizing regulatory elements at cellular and molecular levels in thyrocytes. (25th March 2020) - Sarkar, Deotima; Chandra, Amar K; Chakraborty, Arijit; Ghosh, Sayan; Chattopadhyay, Sreya; Singh, Laishram Hemchandra; Ray, Indrajit
Abstract: Ethnopharmacological relevance: Bamboo shoots (BS) are consumed in various forms and used largely in naturopathy for curing ailments since ancient times to present days. It is eaten in South East Asian countries in several indigenous preparations. In north east India, it is consumed predominantly and used as natural cure to treat various diseases. Although known for its beneficial effects, adverse effects including goitrogenic/antithyroidal potential are emerging. Aim of the study: Endemic goiter exists in Manipur, India even after adequate iodine intake for consumption of BS. It is thus important to study the impact of this goitrogenic food on certain thyroid hormone synthesizing regulatory factors at cellular and molecular level in thyrocytes. Materials and methods: Phytochemical analysis of BS - Bambusa balcooa Roxb (BSBR) extract conducted. IC50 of the extract on thyrocytes in culture was determined. To study the antithyroid effects of this goitrogenic food, activity status of Na + -K + -ATPase, TPO and Deiodinase, mRNA and protein expressions of NIS, TPO and PAX8 were investigated with and without extra iodine in culture media. Simultaneously ROS generation in terms of H2 O2 and antioxidant status, NO, LPO were assayed. Results: Activities of the studied enzymes decreased depending on dose and time with increased H2 O2, decreased antioxidants followed by increased NO with LPO. DNA damage and LDH also increased while mRNA and protein expression of NIS, TPO and PAX8 were downregulated. Extra iodine ameliorated all such effects partially. Conclusions: Bioactive constituents of the extract imbalances oxidative status of thyrocytes impairing action of hormone synthesizing elements at cellular and molecular level. Graphical abstract: Image 1